2015
DOI: 10.18805/ijar.5575
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic effect of non-starch polysaccharide enzymes and synbiotics on performance, nutrient retention, gut health and carcass characteristics of broiler chicken fed corn-soybean meal based low energy diets

Abstract: This study was conducted to evaluate the synergistic effect of NSP enzymes and synbiotics supplementation in a cornsoybean meal based low energy diet. A total of 150 broilers were allocated to five treatment groups. Supplementation of NSP enzymes and synbiotics significantly (P<0.05) improved weight gain and FCR. The BD supplemented with NSP enzymes and synbiotics alone or in combination had no effect on retention of DM, OM, CF, EE, NFE and phosphorus, while CP and GE retention increased (P<0.05). The tibia as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
2
1
0
Order By: Relevance
“…Addition of YCW in broiler diet increases number of useful indigenous bacteria that enhance efficiency of digestion and absorption by stimulating the vascularization and development of intestinal villi (Stappenbeck et al, 2002). Results similar to our findings have been reported by Nyamagonda et al (2011) and Narasimha et al (2015) who observed a better weight gain and FGR in birds supplemented with prebiotic. However data for feed intake is in contrast to 3.76 ± 0.02 3.80 ± 0.03 3.81 ± 0.03 3.86 ± 0.02 Results are presented as mean ± standard error.…”
Section: Resultssupporting
confidence: 92%
“…Addition of YCW in broiler diet increases number of useful indigenous bacteria that enhance efficiency of digestion and absorption by stimulating the vascularization and development of intestinal villi (Stappenbeck et al, 2002). Results similar to our findings have been reported by Nyamagonda et al (2011) and Narasimha et al (2015) who observed a better weight gain and FGR in birds supplemented with prebiotic. However data for feed intake is in contrast to 3.76 ± 0.02 3.80 ± 0.03 3.81 ± 0.03 3.86 ± 0.02 Results are presented as mean ± standard error.…”
Section: Resultssupporting
confidence: 92%
“…All treatments were similar and significantly decreased intestinal pH and viscosity. Narasimha et al, (2015) reported that viscosity in intestinal content was considerably reduced with enzyme or symbiotics (probiotic+prebiotic) addition to basal diet, corroborating with the present findings. Also, Owens et al (2008) reported lower gut viscosity on different feed additives (Allzyme, Avilamycin, Avimos, Biomos, yeast extract, Avizyme, xylanase, Gustar alone or in combination).…”
Section: Resultssupporting
confidence: 92%
“…Günal, et al, (2004) showed that the Avizyme 1300-xylanase or Avizyme 1500-amylase enzymes addition in diets had nonsignificant (p <0.05) effect on the ADG, ADFI, FI, or FCR of chickens. However, Narasimha et al, (2015) reported that supplementation of NSP enzymes to low energy diet significantly reduced (p <0.05) the price feed per kg producing one kg of live body weight and increased growth performance of broilers. Moreover, Zhou et al, (2009) have demonstrated that adding commercial xylanase, a-amylase, and protease multienzyme complex to broiler (38 days of age) diets has enhanced the use of ME, especially in low ME meals.…”
Section: Discussionmentioning
confidence: 97%